(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
In order to limit the production of pollutant gases, the transportation sector, both public and private, has turned its attention to Electric Vehicles (EVs). The most important barrier to commercializing and spreading EVs are the issues regarding the battery. The batteries are heavy, bulky, expensive, and have a limited lifetime. Furthermore, frequent charging and limited operating range due to the low energy density are other obstacles to developing EVs worldwide. Dynamic Wireless Power Transfer (WPT) is a possible solution in order to solve the problems related to the battery. In this solution, the battery of the EV can be charged when the vehicle is in motion. In this kind of charging system, the transmitter coils are embedded into the ground and the receiver coil is installed underneath the vehicle. Through a sufficient charging infrastructure large enough to charge the electric vehicle during driving, the size of the battery onboard can be reduced and the driving range of the EV can be extended. EV and without any establishment of the communication between vehicle and ground, even in the case of lateral misalignment or variations of the air-gap. Subsequently, the complete simulation of the system in static and dynamic charging conditions is performed and the operation in different charging conditions such a variation of the operating frequency, power demand, lateral misalignment, vehicle speed, and air-gap, is studied. The procedure for the construction of the charging lane with the development of the coils, the embedding procedure and implementation of the power electronic converter is presented.